Pengaruh Kecerdasan Intelektual, Kecerdasan Emosional, dan Perilaku Belajar Terhadap Pemahaman Atas Akuntansi Dasar Mahasiswa Dengan Kepercayaan Diri Sebagai Pemoderasi: The Influence of Intellectual Intelligence, Emotional Intelligence, and Learning Behavior on Understanding of Basic Accounting Students with Self-confidence as Moderator - Ningsih, Nur Ayu Setia; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2019)
This study was conducted to analyze and examine the influence of intellectual intelligence, emotional intelligence, and learning behavior toward the preoccupation of basic accounting with self-confidence as a moderating variable. This research was conducted by using student force of accounting class of year 2014. This research uses descriptive quantitative approach that is explained in the form of tables and graphs on the condition of objects and research results with the help of data analysis. Data was collected through questionnaires on 130 respondents taken using slovin formula. In this context research is expected to provide information or knowledge about the influence of intellectual intelligence, emotional intelligence, and learning behavior towards basic accounting understanding with self-confidence as a moderator variable. The results of this study indicate that intellectual acumen and emotional intelligence affect the understanding of accounting. Learning behavior does not affect the understanding of basic accounting. While intellectual intelligence, emotional intelligence, and learning behavior does not affect the basic understanding of accounting with self-confidence as a moderator.